Filmorama: construção de uma visualização de dados baseada em conceitos do design - Mergel, Germano Duarte (Universidade do Vale do Rio dos Sinos, 2011)
This study aims at understanding the concept of data visualization and its creation as well as the analysis of design concepts applied and good practices observed. The method to be adopted in order to meet the proposed goal is based on two moments, the first being the study of design concepts and web design, digital layout, usability and user experience. In a second step, cases of reference data views are seen from the perspective of the issues addressed in the first part of this work. Subsequently, an experiment is proposed and realized in the form of a project to create a website, seeking the application of concepts learned. The expected result is a visualization of information in the form of a site with a high index of usability, pointing to the influence of the concepts studied in the design, and observed in cases of reference, in the visual model created. In the end, an analysis of the results is made for understanding and closure, and a continuation of this work is proposed.
Keywords: Conceito de visualização; Conceitos de design; Diagramação digital; Preview concept; Design concepts; Web design; Digital typesetting